Endobronchial ALK-Positive Anaplastic Large Cell Lymphoma Presenting Massive Hemoptysis - Kim, Hee Kyung; Kim, Bo Hye; Kim, Sae Ahm; Shin, Jae Kyoung; Song, Ji-Hyun; Kwon, Ah-Young; Kim, Jung-Hyun; Kim, Eun-Kyung; Lee, Ji-Hyun; Kim, Gwaung-Il; Jeong, Hye Cheol (Tuberculosis and respiratory diseases, 2015)
Primary anaplastic large cell lymphoma (ALCL) of the lung is highly aggressive and quite rare. We report here a case of anaplastic lymphoma kinase-positive endobronchial ALCL, that was initially thought to be primary lung cancer. A 68-year-old woman presented with hemoptysis, dyspnea, and upper respiratory symptoms persisting since 1 month. The hemoptysis and and bronchial obstruction lead to respiratory failure, prompting emergency radiotherapy and steroid treatment based on the probable diagnosis of lung cancer, although a biopsy did not confirm malignancy. Following treatment, her symptoms resolved completely. Chest computed tomography scan performed 8 months later showed increased and enlarged intra-abdominal lymph nodes, suggesting lymphoma. At that time, a lymph node biopsy was recommended, but the patient refused and was lost to follow up. Sixteen months later, the patient revisited the emergency department, complaining of persistent abdominal pain since several months. A laparoscopic intra-abdominal lymph node biopsy confirmed a diagnosis of ALCL.